Why Islamic Economics ? The Difference Between The Conventional System And The Islamic Economic System - muhammad kambali; Jamiatus Dinny Sholikah; Misella Sandi (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
The presence of an economic system is a real part of the effort to answer the economic problem of what, haw, for whom. Every economic system has different ways and ways of solving these problems. This research aims to answer the main problem, why does it have to be Islamic economics? With the liberal research approach, these problems are discussed starting with data collection based on secondary data in the form of research articles and books related to the main focus of the research. Further data were analyzed using content analysis and comparative descriptive analysis methods. The results of this study indicate that the main reason why an Islamic economic system is needed is that Islamic economics is evident from various historical records starting from the beginning of the Prophet Muhammad. Until now the Islamic economic system is clearly different in answering the economic problems of what, haw, and for whom. The Islamic economic system rests on the principle of values that enable human moral hazard to be minimized by upholding the values of monotheism, justice and balance. While the conventional economic system, capitalism and socialism recorded various negative defects starting from the 1929 crisis, the Subprime Mortgage crisis, the dissolution of the Soviet NEP. The results of this study have implications for strengthening the importance of carrying out economic activities that are based on justice and a balance in life.